2015
DOI: 10.1523/jneurosci.3663-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Relating Cerebellar Purkinje Cell Activity to the Timing and Amplitude of Conditioned Eyelid Responses

Abstract: How Purkinje cell (PC) activity may be altered by learning is central to theories of the cerebellum. Pavlovian eyelid conditioning, because of how directly it engages the cerebellum, has helped reveal many aspects of cerebellar learning and the underlying mechanisms. Theories of cerebellar learning assert that climbing fiber inputs control plasticity at synapses onto PCs, and thus PCs control the expression of learned responses. We tested this assertion by recording 184 eyelid PCs and 240 non-eyelid PCs during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
110
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 57 publications
8
110
0
Order By: Relevance
“…The present results show that individual Purkinje cells can also acquire pause responses to two CSs of different modalities. This is consistent with a recent study in which it was shown that Purkinje cells can acquire pause responses to two tones with different frequencies (36). Next, we examined the effect of presenting two CSs simultaneously, as a compound CS.…”
Section: Discussionsupporting
confidence: 89%
“…The present results show that individual Purkinje cells can also acquire pause responses to two CSs of different modalities. This is consistent with a recent study in which it was shown that Purkinje cells can acquire pause responses to two tones with different frequencies (36). Next, we examined the effect of presenting two CSs simultaneously, as a compound CS.…”
Section: Discussionsupporting
confidence: 89%
“…As summarized in this brief review, the evidence indicates that the domain encompasses both motor and perceptual timing, and is observed in both explicit and implicit tasks. We have highlighted one important constraint, namely that the cerebellum may be required when tasks require timing single intervals, or what we have called event timing [38, 39], but not when timing is inherent to rhythmic or continuous dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in trained animals, lesions of the cerebellar cortex abolish the precise timing; the CR is now time-locked to the CS rather than the US [35]. Eyeblink conditioning has been perhaps the most sophisticated model system for studying the cellular and molecular mechanisms of timing [37, 38*, 39]. …”
Section: The Role Of the Cerebellum In Explicit And Implicit Motor Timentioning
confidence: 99%
“…CRs are believed to be due, at least in part, to “learned” pauses in Purkinje cell firing[29]. The timing of such pauses is matched to the CS-US delay and bears a systematic relationship to the eyelid CR[3033]. Leading models of eyelid conditioning suggest that the pauses emerge as a result of plasticity at parallel fiber synapses[34;35].…”
Section: Functions Of Granular Layer Circuitrymentioning
confidence: 99%